Contribuição ao estudo dos fatores que influenciam na decisão do tomador de financiamento habitual - Lima, Tchaykowsky Adriano (2004)
This work deals with the several types of loan mortgage, within the context of the Brazilian dwelling house system, and their influence on the decision to be taken by the house buyer. The dissertation starts with the historic background of the Brazilian house dwelling problem since the time of the Monarchic until our days. It is also described the importance of the Government Financing Agencies to regulate, to manage and to reduce the deficit of houses in the Brazilian house dwelling system. These agencies are: Banco Nacional da Habitação – BNH, o Sistema Financeiro Habitacional – SF and the Caixa Econômica Federal – CAIXA, which have had large influence in the history and in all other features of the Brazilian house dwelling system. The work focuses the tendencies of the international house dwelling system market, pointing out the success of the American and European models relating them with the programs installed in Brazil, such as the CAIXA program, the private bankers and the building societies loan mortgage systems. An analysis of the risk, financing costs, mortgage payback guarantee, and above of all, the financing protection of the house buyer is also done.